Dapsone Ameliorates Isoproterenol-Induced Myocardial Infarction via Nrf2/ HO-1; TLR4/ TNF-α Signaling Pathways and the Suppression of Oxidative Stress, Inflammation, and Apoptosis in Rats - Abdelzaher, Walaa Yehia; Ahmed, Sabreen Mahmoud; Welson, Nermeen N.; Alsharif, Khalaf F.; Batiha, Gaber El-Saber; Labib, Dina A. Aly (Frontiers in Pharmacology, 2021)
Myocardial infarction (MI) is a critical condition that can happen with high doses or rapid termination of beta blockers therapy. The study aimed to evaluate the potential anti-toxic value of DAP against isoproterenol (ISO) - induced MI. Twenty-eight male Wistar rats were used for the study. The rodents were assigned to four groups (n=7) and the treatments were given for 12 days as follows; Group 1 (control): were administrated normal saline, Group 2 (DAP control): were administrated DAP (10 mg/kg/day IP), Group 3 (ISO group): were administrated ISO (100 mg/kg, IP on the 11th and 12th days of the experiment), and Group 4 (DAP+ ISO): co-treated with DAP plus ISO. The measured parameters were cardiac malondialdehyde (MDA), reduced glutathione (GSH), total nitrite/nitrate (NOx), catalase (CAT), serum cardiac biomarkers; CK-MB, ALT, LDH, and ALK-PH. Also, interleukin-1β (IL-1β), tumor necrosis factor-alpha (TNF-α), Nuclear factor (erythroid-derived 2)-like 2 (Nrf2), heme oxygenase-1 (HO-1), toll-like receptor 4 (TLR4), caspase-3 activity, and hepatic BAX and Bcl-2 were also assessed. Also, histological examination and vimentin immuno-expressions were studied. ISO group exhibited MI as evidenced by the elevation in serum cardiac biomarkers, MDA, NOx, IL-1β, TNF-α, and caspase-3 together with the reduction in GSH, Nrf2, HO-1 levels, and a faint vimentin immuno-reaction. Histological alterations revealing distorted cardiomyocytes; vacuolation, edema, pyknosis, and fragmentation were also noticed. DAP significantly ameliorated all the examined toxicity indicators. DAP revealed efficient ameliorative actions against ISO-caused MI by marked reduction in myocardial infarct size and suppressed oxidative stress, inflammation, and apoptosis via the up-regulation of the Nrf2/ HO-1; TLR4/ TNF-α signaling pathways.